An Eclectic Approach to Arabic Language Education: Implementing Kitab al-Amtsilah at-Tashrifiyah in Modern Indonesian Pesantrens - Hanani, Nurul; Ahid, Nur; Sufirmansyah, Sufirmansyah (Jurnal Pendidikan Islam, 2024)
The importance of effective Arabic language learning methods is increasingly recognized in Indonesia, particularly within modern pesantren. This study aims to explore how the al-Amá¹¡ilah at-Taá¹£rÈ‹fiyyah book facilitates Arabic language acquisition in these educational settings. Employing a qualitative approach, this research utilizes a case study methodology, collecting primary data through interviews with three teachers and three students from Pesantren al-Amien Prenduan and Pesantren Darussalam Gontor. The findings reveal that modern pesantren implement various learning methods, including game-based learning, lingual-based learning, and eclectic-based learning. Specifically, the eclectic method integrates game-based learning with grammar instruction, where teachers provide explanations of Sharaf grammar after students complete reading and memorizing activities. This study concludes that these innovative teaching strategies enhance the effectiveness of Arabic language learning in pesantren environments. The implications of this research suggest that incorporating the eclectic method through the al-Amá¹¡ilah at-Taá¹£rÈ‹fiyyah book can lead to more engaging and effective Arabic language instruction, ultimately benefiting both educators and students. Recommendations for further improving Arabic language teaching methodologies are provided to encourage ongoing development in this critical area of study.